Properties of acid-set queso blanco cheese made with filtered milk products - Blake, Karley Jayne (Kansas State University, 2022)
As the demand for native whey protein ingredients continues to rise outside of the dairy industry, microfiltered milk products like Micellar Casein Concentrate (MCC) are becoming increasingly accessible for cheese production. This increase in microfiltered milk and milk products could cause potential issues within the acid-set cheese industry, as whey proteins often are incorporated within the cheese protein matrix. Thus, this research investigated the impact on functional properties of acid-set cheese produced with MCC using Queso Blanco as a model system. Three replications were completed where cheesemilk was standardized to a 1.2:1 casein-to-fat ratio using rehydrated Milk Protein Concentrate 80 (MPC), Milk Protein Isolate 90 (MPI) or MCC. Data were analyzed with univariate split-plot design methodology (P <0.05) and significant means differentiated with Tukey’s comparisons (P <0.05). Proximate analysis results showed that the three cheeses contained similar moisture (51.18%) and fat (15.13%) contents, but the cheeses made from MPC and MPI standardized cheesemilk had greater protein (~55.2%) content compared with the cheese made from MCC standardized cheesemilk (52.6%) likely due to the lower whey protein content in MCC that carried through to the standardized cheesemilk and resultant cheese. Cheese texture was assessed under 50% strain with a standard double-bite texture profile analysis (TPA) at 10, 30, 50, 70 and 90 days of cheese age. TPA resilience, springiness and cohesiveness showed differences between the cheese made with cheesemilk standardized with MCC vs. the cheeses made with cheesemilk standardized with MPC and MPI, whereas chewiness differed between the cheeses made from cheesemilk standardized with MCC and MPI albeit both were similar to the cheese made with the MPC standardized cheesemilk. Hardness did not show differences among any cheeses. A trained descriptive panel assessed cheeses at 30 and 70 days in a monadic sequential design on a standard 15-point line scale for texture and flavor attributes. No significant differences were detected in organoleptic texture or flavor properties at either day. When assessing for color, a significant difference for whiteness (L*) was found between cheeses made from cheesemilk standardized with MCC and MPI, however, neither differed from the cheese made from cheesemilk standardized with MPC. Cheeses did not differ in red-green color (a*), yellow-blue color (b*), hue angle, or chroma. The change in cheese color was assessed from before to after heating under broiling conditions (225˚C ± 2˚C for 5 minutes) at 10, 30 50, 70 and 90 days. All cheeses exhibited an increase in the degree of color change from pre- to post-heating (ΔE) as the cheeses aged. These results suggest that removing whey proteins via microfiltration before standardizing cheesemilk for acid-set cheese production would not cause noticeable organoleptic or visual differences for consumers; however, there could be implications when converting the cheese to reduced formats like shreds or crumbles.
Keywords: Acid-set cheese; Queso blanco; Micellar casein concentrate